Vulnerability of Antarctic shallow invertebrate‐dominated ecosystems. (7th April 2015) - Clark, Graeme F.; Raymond, Ben; Riddle, Martin J.; Stark, Jonathan S.; Johnston, Emma L.
Abstract: Human impacts threaten not only species, but also entire ecosystems. Ecosystems under stress can collapse or transition into different states, potentially reducing biodiversity at a variety of scales. Here we examine the vulnerability of Antarctic shallow invertebrate‐dominated ecosystems, which may be threatened for several reasons. These unique shallow‐water communities mostly consist of dark‐adapted invertebrates, and rely on sea ice to create low‐light marine environments. Climate change is likely to cause early breakout of seasonal sea ice in parts of Antarctica, which will dramatically increase the amount of light reaching shallow seabed. This is predicted to result in ecological regime shifts, in which invertebrate‐dominated communities are replaced by macroalgal beds. Habitat for these endemic Antarctic ecosystems is globally rare, and the fragmented nature of their distribution along Antarctic coast increases their sensitivity to change. Concurrently, human activities in Antarctica are concentrated in areas where these habitats occur, compounding potential impacts. While there are clear mechanisms of threat to these ecosystems, lack of knowledge about their spatial distribution obscures predictions of potential ecosystem loss, and the likelihood of recovery. In this paper we describe these ecosystems, their association with the environment and the reasons for their vulnerability. We estimate their spatial distribution around Antarctica using sea ice and bathymetric data, and apply the International Union for Conservation of Nature Red List of Ecosystems criteria to assess their vulnerability. Best available data suggest that shallow ice‐covered ecosystems are likely Near Threatened to Vulnerable in places, although the magnitude of risk is spatially variable and requires additional data to strengthen the assessment.